Back Cover: Supramolecular Polymerization of Supermacrocycles: Effect of Molecular Conformations on Kinetics and Morphology (Chem. Eur. J. 22/2017). Issue 22 (14th February 2017) - Yamauchi, Mitsuaki; Adhikari, Bimalendu; Prabhu, Deepak D.; Lin, Xu; Karatsu, Takashi; Ohba, Tomonori; Shimizu, Nobutaka; Takagi, Hideaki; Haruki, Rie; Adachi, Shin‐ichi; Kajitani, Takashi; Fukushima, Takanori; et al.
Abstract : Two supramolecular polymers shown in this cover picture are composed of similar hydrogen‐bonding naphthalene monomers, which differ only by one oxygen atom. Despite structural similarity, these monomers form hexameric supermacrocycles by hydrogen bonding, and further assemble into supramolecular polymer fibers with distinct morphologies (cylindrical vs. helical) by different self‐assembly pathways. More information can be found in the Full Paper by S. Yagai, et al. onpage 5270 ff.